1998
DOI: 10.1182/blood.v92.1.68.413k23_68_75
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Anemia in Myelodysplastic Syndromes With Granulocyte Colony-Stimulating Factor Plus Erythropoietin: Results From a Randomized Phase II Study and Long-Term Follow-Up of 71 Patients

Abstract: Treatment with erythropoietin (epo) may improve the anemia of myelodysplastic syndromes (MDS) in approximately 20% of patients. Previous studies have suggested that treatment with the combination of granulocyte colony-stimulating factor (G-CSF) and epo may increase this response rate. In the present phase II study, patients with MDS and anemia were randomized to treatment with G-CSF + epo according to one of two alternatives; arm A starting with G-CSF for 4 weeks followed by the combination for 12 weeks, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
100
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(113 citation statements)
references
References 25 publications
10
100
0
3
Order By: Relevance
“…Multivariate analysis identified serum EPO <125 U/l as the only pretreatment variable associated with a favourable response to rHuEPO. This cut-off was similar to that previously reported by Rodríguez et al (1998), but lower than the serum EPO level (200 U/l) reported as the optimal cut-off for rHuEPO treatment of the anaemia of the myelodysplastic syndromes (Hellström-Lindberg et al, 1998). In addition, lack of transfusion support at the start of treatment was of borderline prognostic significance.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate analysis identified serum EPO <125 U/l as the only pretreatment variable associated with a favourable response to rHuEPO. This cut-off was similar to that previously reported by Rodríguez et al (1998), but lower than the serum EPO level (200 U/l) reported as the optimal cut-off for rHuEPO treatment of the anaemia of the myelodysplastic syndromes (Hellström-Lindberg et al, 1998). In addition, lack of transfusion support at the start of treatment was of borderline prognostic significance.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, despite some difficulties in comparing the results of our study with those of Hellstroem-Lindberg et al (1998) and Negrin et al (1996), our data lend further support to the concept of a growth factor combination treatment for anaemia in MDS patients.…”
Section: Discussionsupporting
confidence: 74%
“…Using the same response criteria of Negrin et al (1996), we obtained erythroid response rates of 61% (95% CI 41±78) after 12 weeks of cytokine treatment and of 80% (95% CI 59±93) after 36 weeks. If we apply the somewhat stricter criteria of Hellstroem-Lindberg et al (1998) to our data, we find a response rate of 50% (95% CI 31±69) after 12 weeks and 56% (95% CI 35±75) after 36 weeks.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations